The effect of training, development, and job satisfaction on employee performance with the mediating variable of competency (study at pt.wom finance) - Ivana Ivana; Eka Desy Purnama (Institute of Computer Science (IOCS), 2026)
This study aims to examine the effects of training, development, and job satisfaction on employee performance, with competence serving as a mediating variable. Employee performance is a critical factor in achieving organizational goals; therefore, efforts to enhance competence through training and development programs, as well as improving job satisfaction, are essential. This study employed a quantitative approach using a survey method involving employees as respondents. In this study, the population used is all Head Office employees at WOM Finance. The number of indicators used in this study is 15, resulting in a sample size of 15 x 7 = 105 respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that training and development have a positive and significant effect on both competence and employee performance. Job satisfaction has a positive and significant effect on competence but does not have a significant direct effect on employee performance. Furthermore, competence has a positive and significant effect on employee performance and is proven to mediate the relationships between training, development, job satisfaction, and employee performance. These findings suggest that improving employee performance can be achieved more effectively through strengthening employee competence, supported by training, development, and job satisfaction initiatives. Therefore, organizations should optimize competency development programs as a strategic approach to enhancing employee performance. The findings of this study are expected to serve as a reference and basis for consideration for companies in understanding the vital roles that training, development, job satisfaction, and competence play in enhancing performance, thereby enabling the formulation of more effective human resource management strategies.